2014
DOI: 10.1080/10942912.2012.687797
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Olive Fruit Essential Oil: Application of Gas Chromatography-Mass Spectrometry Combined with Chemometrics

Abstract: The extracted Iranian olive fruit essential oil was analyzed using gas chromatography-mass spectrometry. Multivariate curve resolution-alternative least squares approach was used to overcome the problem of background, baseline offset and overlapping/embedded peaks in gas chromatography-mass spectrometry. The analysis of gas chromatography-mass spectrometry data revealed that 90 components exist in the olive fruit essential oil. However, with the help of multivariate curve resolution-alternative least squares t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, terpenes and terpenoids are the main components of essential oils. [9][10][11][12] The volatile fraction of fruits was investigated by means of solid-phase microextraction (SPME), which is considered a suitable analytical technique for the extraction of flavor compounds. SPME meets the requirements of green analytical chemistry as developed by Arthur and Pawliszyn.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, terpenes and terpenoids are the main components of essential oils. [9][10][11][12] The volatile fraction of fruits was investigated by means of solid-phase microextraction (SPME), which is considered a suitable analytical technique for the extraction of flavor compounds. SPME meets the requirements of green analytical chemistry as developed by Arthur and Pawliszyn.…”
Section: Introductionmentioning
confidence: 99%
“…Only fraction S8 showed the presence of elaidic acid, methyl ester (22.15%). This compound, also founded in Iranian olive fruit oil [18], is an esterified form of elaidic acid (fatty acid), which in turn is the trans isomer of oleic acid. Abbey and Nestel [19] reported that elaidic acid increased low density lipoprotein cholesterol (LDL) and decreased high density lipoprotein cholesterol (HDL) in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Extra virgin olive oil (EVOO) contains bioactive compounds such as the main flavonoid, namely luteolin (3,84%) and essential oil of the sesquiterpene group, namely eremophilene (5,20%) as an active compound of phenol derivatives [15,16]. Antibacterial activity in EVOO is caused by the presence of polyphenolic compounds in the form of flavonoids (Fig.…”
Section: Active Compound Contentmentioning
confidence: 99%